Capital social e seu efeito sobre o comportamento do consumidor desenvolvimento e validação de uma escala de mensuração - Cucato, Jussara da Silva Teixeira (2023)
Academic research has not fully investigated the relationship between Social Capital (SC) and Consumer Behavior (CC), particularly when it comes to ways of measuring it, focusing instead on approximations of ways to measure social capital. Studies on SC borrow paradigms from various fields of knowledge such as psychology and sociology. Usually, the field of psychology stands out in studies of SC. However, sociology is increasingly contributing to CC studies. Studies of social groups and theories of social comparison, among others, are evident. However, among the various theories of social groups employed, there is a limitation in studies that employ the SC theory, especially in the relationship between SC and SC, its antecedent and mediating role. The SC that adds to the Social Identity Theory the perspective of networks, and their byproducts, such as solidarity, trust, and ties, more so in a perspective of consumption of what is global versus local. Thus, this doctoral thesis developed in the format of three studies, sequential and complementary, aims to contribute to the research of the SC and its relationship with the SC. It is proposed that the SC, its perspective for groups, and between groups, adds the perspective of formal or non-formal consumer networks, which establish common values and norms of reciprocity of action within the scope of consumption, influencing preferences and evaluations of product, brand or global service consumption. The objective of this thesis is to determine the influence of CS on CC, through an objective way of measuring social capital. The first study is a multiple approach study. It adopts a bibliometric approach, conducted through co-citation analysis, a systematic review and meta-analysis, in order to present a discussion on the current state, possible research directions and empirical evidence of the CS and CC relationship, respectively. The second study contributes to the SC literature by proposing and confirming a CS scale applied to consumers specifically. The third study extends the contribution by empirically testing the CS scale and validating it in a nomological network, exploring its effects on consumer responses such as purchase intention, participation in brand communities, and self-efficacy-self-esteem, also exploring mediating roles. Findings, academic and practical contributions are then discussed.